Penggunaan Alat Pelindung Diri Saat Penyemprotan Pestisida dan Hipertensi pada Petani di Desa Losari Kecamatan Sumowono - Avida Noor Hidayah; Yuliaji Siswanto; Andini Dyah Novita Sari; Annisa Putri Heryanda; Dwi Pamuji Sulistiono (Pro Health Jurnal Ilmiah Kesehatan, 2024)
The use of pesticide products in agriculture can improve the quality and quantity of crops produced. Pesticides have selective poisoning properties, namely killing parasites and pests or insects that carry disease. Mechanisms when spraying pesticides that do not comply with regulations such as not implementing the use of Personal Protective Equipment (PPE) will result in many negative impacts. The impact of pesticides on people who are constantly exposed can cause nervous disorders, liver disorders, hormonal system disorders, and increased blood pressure. Riskesdas 2018 stated that the incidence of hypertension tends to occur more often in people who work as farmers, namely 36.1%. Hypertension can cause complications including heart failure, stroke, kidney damage and vision damage. Causal factors related to increased blood pressure due to exposure to pesticides include not using complete PPE, working period as a farmer, frequency of pesticide spraying and pesticide spraying techniques. The aim of this study was to determine the relationship between exposure to pesticides in terms of use of PPE and the incidence of hypertension in farmers in Sumowono District. The research design was observational analytic with a cross sectional approach. The population used was all vegetable farmers in Losari Village, Sumowono District with a sample of 100 respondents taken using the quota sampling technique. Data on PPE use was collected using a questionnaire and blood pressure using a digital blood pressure monitor, then analyzed using the Chi Square test. The results of the study showed that there was no relationship between the use of PPE and the incidence of hypertension ((p = 0,117; PR = 1,273; 95% CI = 0,969-1,673).). So it can be concluded that the use of PPE was not proven to have a relationship with the incidence of hypertension.   ABSTRAK                 Pemakaian produk pestisida pada pertanian dapat meningkatkan kualitas maupun kuantitas tanaman yang dihasilkan. Pestisida memiliki sifat racun selektif, yaitu membunuh parasit dan hama ataupun serangga pembawa penyakit. Mekanisme pada saat penyemprotan pestisida yang tidak memenuhi aturan  seperti tidak menerapkan penggunaan Alat Pelindung Diri (APD) akan mengakibatkan banyak dampak buruk. Dampak pestisida pada orang-orang yang selalu terpapar dapat menyebabkan gangguan syaraf, gangguan hati, gangguan system hormon, dan kenaikan tekanan darah. Riskesdas tahun 2018 menyatakan bahwa kejadian hipertensi cenderung banyak terjadi pada masyarakat dengan pekerjaan sebagai petani yaitu sebesar 36,1%. Penyakit hipertensi dapat menimbulkan komplikasi diantaranya payah jantung, stroke, kerusakan ginjal dan kerusakan penglihatan.  Faktor penyebab yang berhubungan dengan kenaikan tekanan darah akibat paparan pestisida yaitu tidak menggunakan APD dengan lengkap, masa kerja menjadi petani, frekuensi penyemprotan pestisida dan teknik penyemprotan pestisida. Tujuan penelitian ini adalah untuk mengetahui hubungan antara paparan pestisida yang ditinjau dari penggunaan APD dengan kejadian hipertensi pada petani di Kecamatan Sumowono. Desain penelitian adalah analitik observasional dengan pendekatan cross sectional.  Populasi yang digunakan adalah seluruh petani sayur yang berada di Desa Losari, Kecamatan Sumowono dengan sampel sebanyak 100 responden yang diambil dengan teknik quota sampling. Data penggunaan APD dikumpulkan dengan kuesioner dan tekanan darah menggunakan tensimeter digital, selanjutnya dianalisis menggunakan uji Chi Square. Hasil penelitian menunjukkan tidak ada hubungan antara penggunaan APD dengan kejadian hipertensi (p = 0,117;    RP = 1,273; 95% CI = 0,969-1,673). Sehingga dapat disimpulkan  bahwa penggunaan APD  tidak terbukti memiliki hubungan dengan kejadian hipertensi.